Elaboración de un afiche para reconocer la importancia del lavado de manos - Gonzales Romero, Carmen Nelly (2018)
The purpose of this session is to promote in students the writing of texts, in this case of a discontinuous text such as a poster, with a communicative purpose of encouraging the cleaning and care of the body through the correct washing of hands, promoting in their peers the recognition of the importance of hand washing for health. For this reason, pedagogical and didactic activities have been proposed that, as a whole, seek to achieve the learning expected from fifth grade students of the Santa Rosa de Lima - Talara educational institution, specifically from the competition Write various types of texts in your mother tongue, based on a need and interest of the students, this learning being significant for them. For this reason, it is necessary to consider this type of planning and execution of pedagogical activities that promote not only academic but also formative activities in an integral manner, that is, to motivate the children with their involvement in promoting cleanliness and care of the body, which will make it possible to avoid contracting diseases. It is necessary to specify the pedagogical and didactic strategies to be used in order to achieve the expected learning corresponding to the area of Communication and the competence in mention, where the students will appropriate strategies to shape their proposals in the posters that they will produce in a creative way in order to inform their classmates how important it is to practice hygiene habits, with this they will also demonstrate how indispensable communication is and in this case written communication, whose function will be to give the opportunity to express, argue and encourage in writing, thus fulfilling the students' communicative purpose.